2015
DOI: 10.4238/2015.may.12.6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA haplogroups and somatic mutations are associated with lung cancer in patients from Southwest China

Abstract: ABSTRACT. Mitochondrial DNA mutations play crucial roles in the pathogenesis and progression of human malignancies. Therefore, to determine whether maternal background or mitochondrial DNA somatic mutations were essential cofactors in the lung cancer of Chinese patients as well, the complete mitochondrial DNA displacement loop of the primary cancerous, matched para-cancerous normal and distant normal tissues for 79 Chinese patients with lung cancer were analyzed in this study. Our results indicated that the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Several studies indicated that both normal and cancer cells had equally high levels of heteroplasmy and no significant impact of mtDNA mutations have been observed in human individuals with thyroid, parathyroid, or adrenocortical carcinomas or glioblastoma . On the other hand, detected mtDNA mutations were correlated with head and neck squamous cell carcinoma (HNSCC), endometrial carcinoma (EC), in never smokers, and other lung cancer patients, as well as in individuals with bladder cancer, pituitary adenoma, breast, and skin cancers . Another factor mildly associating somatic mtDNA mutations with MDF is oxidative stress (OS) and some endogenous mechanisms responsible for mtDNA replication .…”
Section: Mdf In Pathological Conditionsmentioning
confidence: 99%
“…Several studies indicated that both normal and cancer cells had equally high levels of heteroplasmy and no significant impact of mtDNA mutations have been observed in human individuals with thyroid, parathyroid, or adrenocortical carcinomas or glioblastoma . On the other hand, detected mtDNA mutations were correlated with head and neck squamous cell carcinoma (HNSCC), endometrial carcinoma (EC), in never smokers, and other lung cancer patients, as well as in individuals with bladder cancer, pituitary adenoma, breast, and skin cancers . Another factor mildly associating somatic mtDNA mutations with MDF is oxidative stress (OS) and some endogenous mechanisms responsible for mtDNA replication .…”
Section: Mdf In Pathological Conditionsmentioning
confidence: 99%
“…Clinically, different ethnic populations show dissimilar susceptibilities to diseases and drug responses (810), and it has been suggested that mtDNA haplogroups may play important roles in these differences (11). Specific mtDNA haplogroups have also been associated with renal, prostate, breast, and lung cancers (1215). In addition, somatic and germline mtDNA mutations, as well as levels of mtDNA copy numbers, have been associated with increased risk of cancer and different responses to anti-cancer drugs (16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we intend to investigate the molecular systematics, population genetics, and biogeographic history of P. f. femoralis using the HVSI gene of mtDNA sequences to definitively solve the mystery. The properties of mtDNA, including their lack of recombination, fast evolutionary rate, maternal inheritance, higher copy number per cell, and higher population-specific polymorphisms, makes them distinct from nuclear DNAs and valuable genetic markers in population genetics study, especially primates (Smith et al 2007;Fang et al 2015;Akbar et al 2016). The HVSI region of mtDNA is primarily chosen because of datasets availability by Meyer et al (2011) for comparative analysis purposes and also this region has proven to be highly informative (Endicott and Ho 2008) and one of the three most variable regions in the D-loop of mtDNA (Malyarchuk et al 2002).…”
Section: Introductionmentioning
confidence: 99%